Clinico‐radiological characteristics of anti‐myelin oligodendrocyte glycoprotein antibody‐associated autoimmune encephalitis in children. (2nd February 2022) - Han, Ji Yeon; Kim, Soo Yeon; Kim, Hunmin; Hwang, Hee; Choi, Jieun; Chae, Jong‐Hee; Kim, Ki Joong; Cheon, Jung‐Eun; Lim, Byung Chan
Abstract: Aim: To investigate the clinical characteristics and prevalence of paediatric anti‐myelin oligodendrocyte glycoprotein (MOG) antibody‐associated autoimmune encephalitis. Method: A total of 94 paediatric patients (46 males, 48 females, median age 9 years 5 months, range: 8 months–17 years 8 months) with autoimmune encephalitis were recruited at Seoul National University Children's Hospital. We evaluated autoantibody status and identified patients with anti‐MOG antibody‐associated autoimmune encephalitis. Retrospective reviews of medical records were performed to describe clinical presentations, laboratory findings, treatments, and outcomes. Results: Eight patients (five males, three females, median age 11 years 9 months) with anti‐MOG antibody‐associated encephalitis were identified (8.5% of those with autoimmune encephalitis), one of whom was copositive for anti‐ N ‐methyl‐d ‐aspartate receptor (NMDAR) antibodies. Anti‐NMDAR antibodies were identified in 23 patients (23 out of 94, 24.5%). Unilateral or bilateral cortical involvement was identified in five patients. Focal contrast enhancement was also identified in three of the five patients with cortical lesions. All patients showed favourable response to immunotherapy with a Modified Rankin Scale ≤2 at the last follow‐up. Relapse was found in one patient and clinico‐radiological remission was achieved with cyclic intravenous immunoglobulin therapy. Interpretation: Anti‐MOG antibody‐associated encephalitis accounts for a significant proportion of clinically defined paediatric patients with autoimmune encephalitis. Anti‐MOG antibody‐associated encephalitis should be included in the clinical spectrum of anti‐MOG‐associated diseases.